LECTURER INSTRUCTIONAL STRATEGIES IN EFL CLASSROOM: CLASSROOM MANAGEMENT PERSPECTIVES - Asriati, Asriati; Muhayyang, Maemuna (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This research aimed at describing the instructional strategies used by the lecturers in knowledge and language skills subjects in English for both instructional and management talks. The method employed was an exploratory descriptive qualitative method in which the observation and open-ended interviews with individuals were conducted. The data resources were lecturer talk in knowledge and skill subjects consisting of seven lecturers. The result of this research shows that the lecturers both in knowledge and language skills employed whole class, group/pair, and individual instructional strategies. The reasons for utilizing them lied on the nature of the subject, the purpose and objectives of each sub course material to scan and see the general ability and the basic interpersonal communication skills of the students in English. Based on these findings, it implicitly takes into account that varying instructional strategies bridge the lecturers to manage their talks in EFL classroom interaction to foster and sharpen the students’ English language development.